2010
DOI: 10.1016/j.physleta.2010.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Gas damping force noise on a macroscopic test body in an infinite gas reservoir

Abstract: We present a simple analysis of the force noise associated with the mechanical damping of the motion of a test body surrounded by a large volume of rarefied gas. The calculation is performed considering the momentum imparted by inelastic collisions against the sides of a cubic test mass, and for other geometries for which the force noise could be an experimental limitation. In addition to arriving at an accurate estimate, by two alternative methods, we discuss the limits of the applicability of this analysis t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 18 publications
(16 reference statements)
9
50
0
Order By: Relevance
“…The torsional drag β rot has been shown to scale inversely to the thermal velocity and thus β rot ∝ m 1/2 0 , with m 0 the molecular mass, validating the rotational dynamics presented here and in Ref. [13], and opening the possibility to measure the effective molecular mass of a mixture of gases without ionization, and directly in moderate vacuum.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The torsional drag β rot has been shown to scale inversely to the thermal velocity and thus β rot ∝ m 1/2 0 , with m 0 the molecular mass, validating the rotational dynamics presented here and in Ref. [13], and opening the possibility to measure the effective molecular mass of a mixture of gases without ionization, and directly in moderate vacuum.…”
Section: Resultssupporting
confidence: 83%
“…By comparison, spinning-rotor gauges measure the torsional drag induced by residual gas on a macroscopic rotor (an idea originally proposed by Maxwell [9]) which in existing devices is generally magnetically levitated. At high vacuum, in the molecular flow regime, such drag can be simply related to the pressure [10][11][12][13], resulting in an absolute calibration. The minimum measurable pressure, approximately 5 × 10 −7 mbar, is usually limited * cblakemo@stanford.edu † Now at SRI International, Boulder, Colorado 80302 by systematic uncertainties or the required integration times [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This noise is amplified by a factor of ∼10 below 100 Hz due to the small gap of 5 mm between the end test and reaction masses [63] (the top view of a test mass and its surroundings is shown in Fig. 7).…”
Section: Squeezed Film Dampingmentioning
confidence: 99%
“…The effective frequencies w m,eff and w f,eff and damping constants g m,eff and f D ,eff introduced in table 1 take the following form The damping constants g m and f D can be expressed in terms of the parameters of the system [56] g p p p p = + + where P is the pressure of the surrounding gas of particles of mass m gas . For the vibrational motion along the symmetry axis the damping rate g m must be substituted by the following expression [56]…”
Section: Appendix B Effective Frequencies and Damping Constantsmentioning
confidence: 99%
“…In general a shear force component will appear in addition to the normal component. Detailed calculations have been carried out analytically for a gas of particles within an infinite volume [56]. For a cube it is found that the ratio of rotational to vibrational noise is a a > ¥  -0.226 gas CSL .…”
Section: Appendix C Analysis Of Lisa Pathfinder Noisesmentioning
confidence: 99%